Taste And Promotion On Purchasing Decisions For Chocolaka Drink Products - Ulfi Aurelia; Andry Stepahnie Titing; Muhamad Stiadi (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The primary aim of this research is two-fold: firstly, to investigate the influence of taste on consumer purchasing behaviour of chocolaka drink products in Kolaka Regency; and secondly, to evaluate the impact of promotional activities on consumer purchasing behaviour of chocolaka drink goods in Kolaka Regency. The present study utilises a quantitative research technique, employing a range of data collection methods such as literature review, observation, and distribution of questionnaires. The population under investigation in this study comprised individuals who regularly consume chocolaka drink items. The sample size for this study was determined to be 100 individuals. This study utilises a research instrument that integrates both a Validity Test and a Reliability Test, employing the statistical programme SPSS 25.0. This study utilises measurement model tests (outer model) and structural model testing (inner model) through the application of Structural Equation Modelling (SEM) with Partial Least Squares (PLS) for data analysis. The study's results indicate a substantial positive correlation between the taste variable and the purchase decision, as demonstrated by a t-statistic value of 3.084 (p = 0.002). In a similar vein, the variable pertaining to promotion exhibits a noteworthy positive influence on the choice to make a purchase, as evidenced by a t-statistic of 5.726 (p = 0.000).